Research of vibrations of vertical component of cutting force during turning - E. V. Artamonov; V. V. Voronin; T. E. Pomigalova (Омский научный вестник)
A method for localizing bands of vertical component of the cutting force in time spectrum during metal turning has been established. The method for determining the source of spectral components is based on the windowed Fourier transform. The powers of the spectral components of vibration signals at different cutting speeds in especially sensitive frequency ranges are compared.